2005
DOI: 10.1152/jn.01306.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Frequency Repetitive Transcranial Magnetic Stimulation on Interhemispheric Inhibition

Abstract: We studied the effects of 1-Hz repetitive transcranial magnetic stimulation (rTMS) on the excitability of interhemispheric connections in 13 right-handed healthy volunteers. TMS was performed using figure-eight coils, and surface electromyography (EMG) was recorded from both first dorsal interosseous (FDI) muscles. A paired-pulse method with a conditioning stimulus (CS) to the motor cortex (M1) followed by a test stimulus to the opposite M1 was used to study the interhemispheric inhibition (ppIHI). Both CS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 54 publications
(84 reference statements)
2
77
1
2
Order By: Relevance
“…Therefore, a possible neurophysiological explanation of short-term non-use effect on transcallosal interaction might deal with changes in the excitability of the population of interneurons that controls both transcallosal and corticospinal neurons, thus inducing similar effects in the two neural systems. In agreement with this hypothesis, it has been shown that the administration of an inhibitory protocol on left M1 by means of rTMS was able to decrease the corticospinal excitability of left M1 and transcallosal pathway activity (i.e., IHI from left to right M1s) (Pal et al, 2005). Furthermore, a reduction in transcallosal pathways activity (LtoR IHI) induced by a corticocortical associative stimulation protocol elicited an increase of the right M1 corticospinal excitability (Rizzo et al, 2009(Rizzo et al, , 2011.…”
Section: Immobilization Effectmentioning
confidence: 52%
“…Therefore, a possible neurophysiological explanation of short-term non-use effect on transcallosal interaction might deal with changes in the excitability of the population of interneurons that controls both transcallosal and corticospinal neurons, thus inducing similar effects in the two neural systems. In agreement with this hypothesis, it has been shown that the administration of an inhibitory protocol on left M1 by means of rTMS was able to decrease the corticospinal excitability of left M1 and transcallosal pathway activity (i.e., IHI from left to right M1s) (Pal et al, 2005). Furthermore, a reduction in transcallosal pathways activity (LtoR IHI) induced by a corticocortical associative stimulation protocol elicited an increase of the right M1 corticospinal excitability (Rizzo et al, 2009(Rizzo et al, , 2011.…”
Section: Immobilization Effectmentioning
confidence: 52%
“…Schnitzler et al (1995), using magnetoencephalography (MEG), reported that concurrent tactile stimulation of the ipsilateral hand enhances the response of SI to stimulation of the contralateral median nerve. Conversely, (1) Korvenoja et al (1995) reported that the SI activation (detected using MEG) evoked by contralateral median nerve stimulation is suppressed during ipsilateral hand movement, (2) functional magnetic resonance imaging studies in both monkeys (Lipton et al, 2006) and humans (Hlushchuk et al, 2006) showed that an ipsilateral skin stimulus evokes CNS actions that partially suppress the SI response to a contralateral stimulus, (3) destruction of SI in one hemisphere (rats) was shown to be accompanied by the appearance (in the opposite SI) of neurons with bilateral receptive fields [interpreted to indicate that SI activity exerts a suppressive influence on SI neurons in the opposite hemisphere (Pluto et al, 2005)], and (4) low-frequency transcranial magnetic stimulation of sensorimotor cortex (in humans, Pal et al, 2005) was found to reduce excitability in the opposite hemisphere. Viewed collectively, these findings raise the possibility that the response of the SI hand region to a tactile stimulus (and thus the stimulus-evoked perceptual experience) may be subject to modulatory influences arising from the ipsilateral hand.…”
Section: Introductionmentioning
confidence: 99%
“…This technique allows the noninvasive evaluation of interhemispheric inhibition in humans, providing complementary information to that obtained using functional neuroimaging, EEG and MEG in cognitive neuroscience. Pal et al (2005) now demonstrate the possibility of modulating IHI in healthy human subjects using inhibitory 1-Hz rTMS. These findings provide a methodological tool to explore a variety of exciting hypotheses in human motor control and cognitive processing.…”
mentioning
confidence: 72%
“…Downregulation of activity in one motor cortex using 1-Hz repetitive transcranial magnetic stimulation (rTMS) (Chen et al 1997) results in decreased IHI over the opposite motor cortex that outlasts the period of stimulation. Pal et al (2005) studied IHI at rest using a paired-pulse technique. A suprathreshold conditioning TMS stimulus (CS) applied to one M1 is followed a few milliseconds later by a second suprathreshold test stimulus (TS) delivered to the opposite M1 (Ferbert et al 1992).…”
mentioning
confidence: 99%